(untitled) (Western European Journal of Medicine and Medical Science, 2024)
The main principle of epilepsy treatment is the long-term regular use of antiepileptic drugs (AEDs) to reduce the frequency of seizures or their complete reduction in the absence of clinically significant side effects. Important importance is given to the issues of tolerability of antiepileptic therapy and the problem of compliance - the patient’s desire to correctly fulfill the recommendations of doctors, the presence of mutual understanding between the doctor and the patient, as well as his relatives and friends.